2008
DOI: 10.1016/j.jsat.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in an integrated trauma-focused intervention for women in community substance abuse treatment

Abstract: A substantial number of women who enter substance abuse treatment have a history of trauma and meet criteria for Post Traumatic Stress Disorder (PTSD). Fear regarding the extent to which PTSD treatment can evoke negative consequences remains a research question. This study explored adverse events related to the implementation of an integrated treatment for women with trauma and substance use disorder (Seeking Safety) compared with a non-trauma focused intervention (Women's Health Education). Three hundred fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
(27 reference statements)
2
22
0
1
Order By: Relevance
“…PTSD and PD) and substance use (Zahradnik and Stewart 2009). For example, a considerable number of women who enter treatment for substance abuse report a trauma history and/or meet criteria for PTSD (Killeen et al 2008). Similarly, we found a significant association between GAD and increased cigarette smoking post typhoon.…”
Section: Discussionsupporting
confidence: 60%
“…PTSD and PD) and substance use (Zahradnik and Stewart 2009). For example, a considerable number of women who enter treatment for substance abuse report a trauma history and/or meet criteria for PTSD (Killeen et al 2008). Similarly, we found a significant association between GAD and increased cigarette smoking post typhoon.…”
Section: Discussionsupporting
confidence: 60%
“…No adverse events were reported in Boden et al (2012) and Norman (unpublished). Hien et al (2009) reported 83 study related adverse events from 353 participants (reported in Killeen et al, 2008). No differences were found in the number of events experienced between the two conditions (RR 1.13; 95% CI 0.88 to 1.45).…”
Section: Group-based Non-trauma-focused Interventionmentioning
confidence: 99%
“…For these theorists, tracing unintended social repercussions is perhaps the most crucial element in the study of social phenomena 5 6. However, the assessment of unintended and adverse effects remains a neglected topic in evaluations of public health interventions7 other than in areas such as suicide prevention and illicit drug interventions 8 9. Since harms are generally not measured in a consistent manner across studies, they are rarely examined in systematic reviews 7 10.…”
Section: Introductionmentioning
confidence: 99%